2x+5y+9z+3x+2y-6z-4x-7y+2z=

Simple and best practice solution for 2x+5y+9z+3x+2y-6z-4x-7y+2z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+5y+9z+3x+2y-6z-4x-7y+2z= equation:


Simplifying
2x + 5y + 9z + 3x + 2y + -6z + -4x + -7y + 2z = 0

Reorder the terms:
2x + 3x + -4x + 5y + 2y + -7y + 9z + -6z + 2z = 0

Combine like terms: 2x + 3x = 5x
5x + -4x + 5y + 2y + -7y + 9z + -6z + 2z = 0

Combine like terms: 5x + -4x = 1x
1x + 5y + 2y + -7y + 9z + -6z + 2z = 0

Combine like terms: 5y + 2y = 7y
1x + 7y + -7y + 9z + -6z + 2z = 0

Combine like terms: 7y + -7y = 0
1x + 0 + 9z + -6z + 2z = 0
1x + 9z + -6z + 2z = 0

Combine like terms: 9z + -6z = 3z
1x + 3z + 2z = 0

Combine like terms: 3z + 2z = 5z
1x + 5z = 0

Solving
1x + 5z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5z' to each side of the equation.
1x + 5z + -5z = 0 + -5z

Combine like terms: 5z + -5z = 0
1x + 0 = 0 + -5z
1x = 0 + -5z
Remove the zero:
1x = -5z

Divide each side by '1'.
x = -5z

Simplifying
x = -5z

See similar equations:

| -4x^2+11x-6=0 | | 4+6x=40+15x | | 9x^4+33x^3-71x^2-57x-10=0 | | 11-30t-2t^2=0 | | -21=-7(2+5v)-7 | | 7x^2+7x-14=0 | | 5c+4v=38 | | -8=-8+4(-2-2v) | | x^2+56=-x | | -4-5n=-3n+5+1 | | 16=4(a-3) | | -48=6(2x+5)+x | | (x+2)(x-6-2i)(x-6+2i)=0 | | -14=3x+-2 | | -13=-(v+4)-8v | | (-2x)(2x)= | | 4.9x^2-40x+80=0 | | -7+4b=2+b | | 65+2x+34-x=3x+12-4x-23 | | 5n-16-8h=-10 | | 88=240t-16t^2 | | 9x^4+33x^3-71x^2-10=0 | | 3x^3-43x^2+188x-228=0 | | 72=-6r | | 7x+5=3x+17 | | 7k-14+3k=21 | | 5w^4+5w^2+15w= | | 5x+5=3x+17 | | 3y-4+y+48=7y+50-5y | | y=(2x^2)+x-10 | | 7x+3=x+21 | | 4.8+1.1n=2.38 |

Equations solver categories